FIDUSIA SEBAGAI JAMINAN PEMBIAYAAN DITINJAU DARI SEGI KEAMANANNYA DALAM PRAKTEK DI PERUSAHAAN PEMBIAYAAN PT. FIFGROUP TENGGARONG - Febby Aristia Andriani (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT The right to acquire the remaining insurance payments occur in the case of a pure loss of the motor vehicle as collateral and objects mentioned in the events covered by insurance in the financing agreement. In this case PT. FIFGROUP entitled to file an insurance claim to the insurance company Astra Buana who have collaborated on consumer financing. From the funds of insurance claims in the melt by the insurance company would cover the remaining debt and dependents consumers at afford it, while the excess of the remaining funds disbursed will be given to the consumer as an insurance claim funds. With the events covered by the insurance contract or objects such as loss of goods fiduciary and completion of calculations on insurance claims and the entire debt financing terlunasinya consumers, fiduciary collateral financing agreement will end. It is a manifestation of the protection of goods fiduciary in view in terms of safety. Debtor or consumer who has transferred the right to object fiduciary to a 3rd party without consent from PT. FIFGROUP are defaults on the financing arrangements that have been made by both parties to the agreement. During the installment payments goes smoothly and is not constrained, then the PT. FIFGROUP will not take action to secure the unit collateral, but by taking the way of deliberation and consensus amicably with the assignor fidusianya collateral to another party to perform over the contract or over financing. Whereas in matters relating to the financing nunggak problems can be resolved by deliberation and kinship between PT. FIFGROUP, the debtor or the consumer according to the agreement the agreement, but if the state was forced PT FIFGROUP will use the services of law enforcement authorities, as a companion as well as a mediator to resolve the dispute between the two sides to reach a consensus.